Excision and Regional Flap Reconstruction with Radiation Therapy of Granuloma Annulare of the Digit: A Case Report - Austin Jiang; Linda K Green; David Terence Jonathan Netscher (Archives of Plastic Surgery)
Granuloma annulare (GA) is a benign, often self-limited granulomatous skin condition that typically resolves spontaneously. Treatment is often not required but topical and injectional corticosteroids are the most common interventions. Excision is effective for diagnosis and temporary treatment but usually not considered curative. This case report describes unconventional treatment of a recurrent biopsy proven granuloma annulare of the index finger. Due to the combination of the recalcitrant nodules interfering with function and patient preference, the nodules were excised multiple times. Ultimately requiring reconstruction with a pedicled radial forearm flap, the patient thereafter received radiation therapy to prevent recurrence, the combination of which has not been previously described in the literature. The patient was treated successfully without evidence of recurrence at 18 months.